A cross-sectional study to assess the knowledge, attitude, and practices towards road traffic safety regulations among college going students of himalayan region, Uttarakhand, India - Swati Sharma; Neha Sharma; Shaili Vyas; Jayanti Semwal (Wolters Kluwer Medknow Publications, 2020)
Background: As per WHO, nearly 1.33 million people die every year due to road traffic accidents (RTAs) all over the world. 10% of the annual average of road traffic accidents cases occurs in India. Aims and Objective: To determine the knowledge, attitude and practices related to road safety rules among college students. Methodology: A descriptive cross-sectional study was conducted on 102 college students through a pre-tested questionnaire. Statistical Package for Social Sciences (SPSS version-23) software, Chicago, USA, was used for data analysis. Results: 91.3% of the college students knew the right age for getting a driving license but only 24.5% students responded correctly for the blood alcohol concentration while driving. Most of the study participants had good attitude towards road traffic rules and regulations, driving license, road signs & symbols. 63-65% of the study participants responded that they always wear belt or helmet while driving and keep a specific speed limit while driving, and never used mobile phone or play loud music while driving. Conclusion: RTAs can be minimized by strict enforcement of regulations by the road traffic police and through frequent road traffic awareness. But the self-responsibility by the drivers should also be there to bring about drastic change in minimizing RTAs.